2016
DOI: 10.1016/j.gca.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Deposition, accumulation, and alteration of Cl−, NO3−, ClO4− and ClO3− salts in a hyper-arid polar environment: Mass balance and isotopic constraints

Abstract: The salt fraction in permafrost soils/sediments of the McMurdo Dry Valleys (MDV) of Antarctica can be used as a proxy for cold desert geochemical processes and paleoclimate reconstruction. Previous analyses of the salt fraction in permafrost soils have largely been conducted in coastal regions where permafrost soils are variably affected by aqueous processes and mixed inputs from marine and stratospheric sources. We expand upon this work by evaluating permafrost soil/sediments in University Valley, located in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 57 publications
7
73
0
Order By: Relevance
“…calculated between the 2010 snow surface and the volcanic sulfate deposition from the eruption of Mt. This data are similar to the range and variability of perchlorate thatJackson et al [2016] reported in surface snow in the McMurdo Dry Valleys, Antarctica. The snowpit covers the time period from 1967 to 2010.The WAIS Divide snowpit was dated by counting annual summertime non-sea-salt (nss) sulfate concentration maxima[Cole-Dai et al, 2009] (Figure S4).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…calculated between the 2010 snow surface and the volcanic sulfate deposition from the eruption of Mt. This data are similar to the range and variability of perchlorate thatJackson et al [2016] reported in surface snow in the McMurdo Dry Valleys, Antarctica. The snowpit covers the time period from 1967 to 2010.The WAIS Divide snowpit was dated by counting annual summertime non-sea-salt (nss) sulfate concentration maxima[Cole-Dai et al, 2009] (Figure S4).…”
supporting
confidence: 85%
“…Measurement of perchlorate in snow and ice will likely yield both short and long records of perchlorate in the environment. In addition, it is not known if the perchlorate trends found in the Arctic also exist in Antarctica, as few measurements have been made for perchlorate in Antarctic snow [Jackson et al, 2016;Jiang et al, 2013]. The investigations on perchlorate in Arctic snow suggest that perchlorate concentrations appear to be higher in recent snow (post-1980) than in older snow with the increase possibly attributable to anthropogenic influence [Peterson et al, 2015b].…”
Section: Introductionmentioning
confidence: 99%
“…OSL ages obtained from permafrost cores from four polygons in upper and middle University Valley (P1, P2, P8, P12) yielded ages of 17.9 ± 1.6 kyr for sediments at 2–5 cm depths, whereas those at 90–95 cm depths were dated to 170 ± 36 kyr (Lacelle et al, ; Trinh‐Le, ). These ages fit reasonably well with those derived from chloride accumulation in the upper 56 cm of sediments (Jackson et al, ). The undifferentiated till, which contains granite erratics, is probably associated with the Taylor 4b Drift (>2.7 Ma) or an older glaciation (Cox et al, ; Dickinson et al, ).…”
Section: Study Areasupporting
confidence: 81%
“…Apparent rates of ground‐ice accumulation in the icy permafrost were calculated by dividing the cumulative volume of water in the core by the surface area of core barrel and by age of the soils, estimated from OSL ages and chloride concentrations (Lacelle et al, ; Jackson et al, ). Since chloride‐derived ages were obtained for the top 56 cm of soils, the cumulative volume of water was calculated to this depth for sites with cores equal or longer than 56 cm (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…This favors the release of NO x depleted in 15 N and can explain the extremely low aerosol δ 15 N(NO 3 − ) values found during periods of sunlight. The exportation out of the continental ice sheet of this locally produced NO 3 − with extremely low δ 15 N(NO 3 − ) values may explain the low δ 15 N(NO 3 − ) values observed in the Antarctic Dry Valleys region (Jackson et al, ; Michalski et al, ).…”
Section: Discussionmentioning
confidence: 99%